The perceptions of prospective ICT teachers towards the integration of 3D printing into education and their views on the 3D modeling and printing course - Üçgül, Memet; Altıok, Serhat (Education and information technologies, 2023)
3D printing technology has an influence on a variety of industries such as automotive, engineering, medical, aerospace, sports, fashion, education, and more. In education, 3D printing is used in many different fields like pharmacy, mathematics, biology, chemistry, art education, graphic design, engineering, and even in early childhood and special education. The adoption of 3D printing technology in education is still at a low level, and the lack of adequate technology education is considered a major obstacle to the adoption of this technology. As teachers’ knowledge of 3D printing technology increases, so will their intention to integrate 3D printing technologies into their classrooms. However, current teacher education programs have not provided sufficient training to trainees with the necessary expertise and skills to use digital fabrication in the classroom. This case study explored prospective information and communication technologies (ICT) teachers’ perceptions on the integration of 3D printing into teaching and learning as well as their evaluation of offered 3D modeling and printing course. The results showed that most of the prospective teachers were satisfied with the course and they felt competent enough about 3D printing processes and to integrate 3D printing in teaching-learning activities. They have positive opinions about the use of 3D printers for educational purposes, as they provide concretization of the subject, increase the motivation of the students, and they are very useful in the production of teaching materials. In line with the research results, suggestions were made for a course that aims to introduce 3D printing technologies in teacher education programs.